Effects of Aluminum in Metallization Paste on the Electrical Losses in Bifacial N-type Crystalline Silicon Solar Cells. (November 2016) - Aoyama, Takayuki; Aoki, Mari; Sumita, Isao; Yoshino, Yasushi; Ogura, Atsushi
Abstract: Silver/aluminum (Ag/Al) paste has been used as metallization for p + emitter of n-type solar cells. Nevertheless, the Ag/Al paste induces junction current leakage or shunting in the solar cells, resulting loss in open circuit voltage (Voc ). However, the details still are not known about how glass frit and aluminum in the paste affect the p + emitter, and result in the electrical losses, respectively. Furthermore, it is not still clear whether and how the aluminum addition induces the electrical losses. In this study, the "floating contact method" proposed by R. Hoenig was applied for the measurement to investigate the respective effect of glass frit and aluminum on the electrical losses. Conductive paste with the glass frit for the p + emitter induces loss in Voc of the cells even if the paste contains no aluminum. The glass frit in the Ag/Al paste induces carrier recombination and significant shunting of p-n junction, but the aluminum in the paste mitigates these electrical losses because of weakening emergence of Ag-crystallites on the p + emitter.